Nutritional composition and sensory properties of oyster mushroom-based patties packed with biodegradable packaging - Wan Rosli, W.I.; Solihah, M.A. (Universiti Kebangsaan Malaysia, 2014)
The increase use of synthetic packaging films in food products has led to serious environmental problems due to their total non-biodegradability property. Nutrient composition and sensory acceptability of chicken patties formulated with various levels of Pleurotus sajor-caju popularly known as grey oyster mushroom (OM) and wrapped with degradable plastic were studied. The chicken patties were formulated with either 0, 25 or 50% of fresh OM. The results showed that chicken patty formulated with 25% PSC has protein content of 17.46% lower than the control patty which had 18.13% but it was not significant (p>0.05). After storage, cooked chicken patty formulated with 25% OM had protein content of 21.53% lower than the control patty (23.90%) but it was not significant (p>0.05). However, incorporation of OM in chicken patties resulted in decreasing of fat content significantly (p≤0.05) from 15.58 (control) to 13.33% after storage. On the other nutrient, the concentration of β-glucan were detected at values ranged between 0.70 and 0.76 (g/100 g) after 6 month. Other results showed that patty formulated with 25% OM received the highest scores for all attributes except for aroma. Meanwhile, patty prepared with 50% OM received the highest score of aroma attribute after 6 month of storage. However, the score values for all attributes of all OM-based patties were not statistically different with control patty (p> 0.05). In conclusion, the addition of OM at 25% can be recommended for the purpose of lowering fat content while keeping protein and β-glucan unchanged without jeopardizing sensorial properties. This investigation therefore, suggested that biodegradable plastic can be used in packing any type of processed meat-based products.